Developments in Islamic legal maxims and their application to financial transactions - Faruq, Abu Umar; Osmani, Noor Mohammad; Shahed, A.K.M.; Karim, Fazlul (2009)
The practices of contemporary Islamic finance have been mounted with criticisms that are assumingly based on lack of incorporating the maqasid (goals and objectives) of Shari`ah and failure to extrapolate all sources available for ‘dynamising’ the Islamic legal theory and practice. Islamic legal maxims is one of the sciences which aphoristically subsume all the spectrums in which the purpose of Shari`ah is promoted. There are five basic Islamic legal maxims on which the tenet of Shari`ah is based. Some are of general application, while others apply to a particular area of Islamic Jurisprudence including fiqh al-mu`amalaat (the jurisprudence of financial transactions). One such maxim which is reflected in this notion is a particular activity is permissible unless there is a clear prohibition against it. The study is aimed inter-alia to address how the application of the legal maxims to financial transactions can be explored to respond to criticisms mounted about Islamic finance practices.